La agricultura familiar en la parroquia olmedo del cantón Cayambe - Ecuador 2014 - Beltrán Gallardo, Nelson Janss (2015)
Globally, "Family Agriculture (FA)" is considered as the one with the most potential to increase food supply, reduce unemployment, reduce poverty in Latin America and the Caribbean ( LAC ) , protect agricultural biodiversity in the world , make sustainable use of natural resources and linked to food security , considering this as a key for the development of alternative approaches to production as agro-ecology. Based on these, the FAO named year 2014 as the International Year of Family Farming (IYFF). It is estimated that farms belonging to the FA in Latin America increased to about 17 million and grouped to a population of about 60 million people. Despite all these wealth of attributes assigned to the FA, one of the challenges that is currently facing is the great diversity of both definitions and characteristics that have been granted, adding to it the focus, which varies substantially from country to country and within each of these. Therefore, Agustin Ortiz head of the Americas section of the World Rural Forum, proposed that in each of the countries the current agricultural model need to be identified and set to the FA. For these reasons, the present study sought to analyze the current situation of family farming in the parish Olmedo of canton Cayambe in the province of Pichincha through the research of their social, ecological and economic dimensions to provide objective factors as input for the definition and construction of public policy. The methodology used consisted in the application of 184 surveys distributed in 9 communities that conform the parish, the questionnaire involved a total of 65 indicators relating to environmental, productive technical, socio-cultural and economic indicators. The data collected shows that the composition of families of the parish Olmedo is very diverse, ranging from those formed by a single member, to those in which three generations are present.